Carotenoids and Polyphenols Synergistically Balance Skin Response to UV (P02-007-19). (13th June 2019) - Hermoni, Karin Linnewiel; Sharoni, Yoav
Abstract: Objectives: To demonstrate that the combination of carotenoids and polyphenols produce a synergistic photo-protective effect from UV-induced damage to skin cells. Mechanistically, this can be partially explained by modulation of the NFkB and antioxidant response element/Nrf2 (ARE/Nrf2) transcription systems that are important in this process. Methods: In skin keratinocytes and fibroblasts, we analyzed the effects of carotenoids and polyphenol combinations on ARE/Nrf2 and NFkB transcriptional activity (measured by reporter gene assays), as well as on UVB-induced IL-6 and matrix metalloproteinase (MMP-1) expression (measured by ELISA). Results: A combination of Tomato Nutrient Complex (containing lycopene) with rosemary extract (containing carnosic acid) synergistically inhibited NFkB and activated ARE/Nrf2 transcription systems in epidermal keratinocytes and dermal fibroblasts. This combination of phytonutrients also synergistically inhibited the UVB-induced release of the cytokine IL-6. Inflammatory cytokines such as IL-6 and TNFα induce the expression of MMPs, which leads to collagen breakdown. We found that MMP-1 secretion was induced in human dermal fibroblasts by the pro-inflammatory cytokine TNFα. Pre-treatment of these cells with carnosic acid resulted in reduced MMP-1 protein levels. These in-vitro results suggest beneficial effects of phytonutrient combinations on skin health. To assure that, clinical experiments to prove such effects in humans are feasible, we checked the human bioavailability of carotenoids from Tomato Nutrient Complex and found nearly a two-fold increase in their plasma concentrations. Conclusions: This study demonstrates that combination of dietary carotenoids and polyphenols synergistically inhibit UV-induced skin cell damage. The NFKB and ARE/Nrf2 transcription systems are likely involved in these effects. Funding Sources: Lycored.